Early Head Specification in Xenopus laevis - Blue B. Lake; Kenneth R. Kao (The Scientific World Journal)
The head represents the most dorsal and anterior extent of the body axis. In Xenopus, the progressive determination of the head is an extremely complex process involving the activation and localized antagonism of a number of interdependent intracellular signaling pathways including the Wingless/Int-1 (Wnt), bone morphogenetic protein (BMP), and nodal-related pathways. The sequence of events that specify the head are: dorsal-ventral polarization and head organizer specification in the blastula; gastrulation; neural induction; and patterning of the anterior-posterior and dorsal-ventral neuraxes. Wnt signaling is required for the specification of the dorsal side initially but is then inhibited within the organizer once it has formed. Similarly, Wnt signaling is required along the length of the neural tube, but must be suppressed at its rostral end for normal brain development. Nodal signaling is also necessary for induction of the mesendoderm, but is subsequently suppressed in its dorsal-anterior extreme to specify head organizer. BMP signaling is required for ventral mesoderm and non-neural ectoderm, and must also be suppressed in the head organizer region and for the differentiation of the ventral midline of the neural tube. Thus, development of the head, and indeed the body plan in general, requires precisely timed and spatially restricted activation and repression of these signaling pathways.